Can a preferential trade agreement benefit neighbor countries without compensating them? - Masahiro Endoh; Koichi Hamada; Koji Shimomura (Yale University, Economic Growth Center, 2008)
PTAs are generally negotiated without any tariff concessions or transfers to non-member countries. Can such a PTA benefit the neighbors' welfare? In a two-good competitive equilibrium model in the absence of an entrepôt, a PTA without concessions to the outside will hurt the outsider's welfare when goods are normal. If one of the member countries is an entrepôt, however, it definitely improves the neighbors' welfare. In a multiple-good model, a PTA without concessions deteriorates the neighbors' welfare, provided that all the goods are normal and substitutes, and that initial tariff levels are small.
Keywords: F11; F13; F15; 330; PTA; neighbor's welfare; Kemp-Wan theorem; WTO; GATT article 24; Entrepôt